THE EFFECT OF COMMUNITY LIFESTYLE IN DECIDING TO CHOOSE DIPARANU RUCITRA APARTMENT - Briantito Adiwena; Ispurwono Soemarno; Muhammad Faqih (Journal of Architecture&ENVIRONMENT, 2014)
Property growth of 12% - 20% throughout the year 2012. In Surabaya, the growth the property can reach above 15%. But the lack of residential land in Surabaya, the property developers began to turn to the concept of vertical housing, one of which was an apartment. The development of apartments in Surabaya is inseparable from economic development and people's lifestyles. The public interest in the apartments is very high. The level of the average apartment sales had reached about 80-90 percent. However, the occupancy rate of apartments in Surabaya on average is still below 50 percent. Diparanu Rucitra apartments (DR Apartemen), is the first middle-class apartments that sell an apartment complete with furniture.This research is a quantitative study with a cross-tabulation method. The study aims to explain the relationship between the phenomenon of lifestyle apartments with the decision to choose DR Apartemen. Cross-tabulation method to look for similarities and differences in lifestyle of the owners / tenants who inhabit the owner who does not occupy DR Apartemen.The survey results revealed that there is influence people's lifestyles in the decision to choose either the residential DR Apartemen or as an investment asset. There are some differences and similarities that people's lifestyles in terms of the approach to activities, interests and opinions.